Incidence of superimposed preeclampsia among pregnant Asian women with chronic hypertension - Dittakarn Boriboonhirunsarn; Apichaya Pradyachaipimol; Boonlert Viriyapak (Taylor & Francis Group, 2017)
Objective: To determine the incidence and associated factors of superimposed preeclampsia among pregnant women with chronic hypertension. Methods: A total of 300 pregnant women diagnosed with chronic hypertension were reviewed. Data were retrieved from medical records, including obstetric data, characteristics of hypertension, and pregnancy outcomes. Incidence of superimposed preeclampsia was estimated. Various characteristics were compared to determine associated risk factors. Results: Mean age of the cohort was 34.3 years, 47% were nulliparous, 50% had hypertension before pregnancy, and the others presented with hypertension before 20 weeks. Incidence of superimposed preeclampsia was 43.3% (95% confidence interval (CI) 37.8-48.9). Women with superimposed preeclampsia were significantly more likely to have mean arterial pressure (MAP) ≥105 mmHg at 18-20 and 24-28 weeks. Adverse neonatal outcomes were significantly more common among women with superimposed preeclampsia, including small for gestational age, low birth weight, asphyxia, and neonatal intensive care unit admission. Logistic regression analysis demonstrated that only MAP ≥105 mmHg at 24-28 weeks was independently associated with the increased risk of superimposed preeclampsia by 1.8-fold (adjusted OR 1.8, 95% CI 1.1-3.1, p = 0.031). Conclusion: Incidence of superimposed preeclampsia was 43.3% among pregnant women with chronic hypertension, with increased adverse neonatal outcomes. High MAP ≥105 mmHg during late second trimester might be an important predictor of the condition.